2016
DOI: 10.4236/jss.2016.47002
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Quality Control of Reputation-Based on Incentive Service-Oriented Manufacturing Network

Abstract: Manufacturing enterprises, manufacturing services and customer constitute the service-oriented manufacturing dynamic network (SMN). The quality of SMN mainly depends on the service module provider. Under the condition of information asymmetry in the market, service module provider pursuits for self-interest maximization, may take quality speculation. Based on the reputation incentive theory, this paper establishes an optimal SMN node quality behavior dynamic model of the contract which combines with dominant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Jin Cao, Zhibin Jiang, Kangzhou Wang (2016) studied customer demand forecasting for service-oriented manufacturing based on customer satisfaction [30]. Liangqing Feng, Kunkun Zeng, Fangling Shu (2016) studied the problem of reputation quality control in manufacturing networks based on incentive services, and proposed an optimal dynamic model of quality behavior in manufacturing dynamic network nodes [31]. Liu Zhiyong, Li Bizhen, Ye Songzhong, Yang Shaoxiong and others (2016) studied the different paths of service-oriented manufacturing development of Fujian sports goods manufacturing enterprises [32].…”
Section: Research On Service-oriented Manufacturing Industrymentioning
confidence: 99%
“…Jin Cao, Zhibin Jiang, Kangzhou Wang (2016) studied customer demand forecasting for service-oriented manufacturing based on customer satisfaction [30]. Liangqing Feng, Kunkun Zeng, Fangling Shu (2016) studied the problem of reputation quality control in manufacturing networks based on incentive services, and proposed an optimal dynamic model of quality behavior in manufacturing dynamic network nodes [31]. Liu Zhiyong, Li Bizhen, Ye Songzhong, Yang Shaoxiong and others (2016) studied the different paths of service-oriented manufacturing development of Fujian sports goods manufacturing enterprises [32].…”
Section: Research On Service-oriented Manufacturing Industrymentioning
confidence: 99%
“…This model has become the standard theory of repeated game models. In terms of reputational incentives, Feng et al (2016) found that reputation incentive can positively influence the service module provider’s effort level in manufacturing enterprises. Özdogä an (2014) constructed a repetitive game model with incomplete information.…”
Section: Introductionmentioning
confidence: 99%